Geochemical characteristics and mechanisms of densification of pre-Jurassic crude oil in the Tainan Sag, Turpan-Hami Basin, China - Yaao Chi; Bo Liu; Yuchu Chen; Boyang Wang; Longhui Bai; Liu Wang; Yaohui Xu (Unconventional Resources, 2022)
Large volumes of heavy oil were distributed in the pre-Jurassic strata of Tainan sag, Turpan Hami Basin, China. The geochemical characteristics and origins of heavy oil are of great significance to future exploration in the region. This study classified crude oil using data on its physical properties, group composition, and biomarker compounds. Further, the distribution of different types of crude oil in lateral and vertical directions are clarified. Mechanism of densification of crude oil in the study area was aslo summarized. Results indicate that there are four categories of crude oil with different densities in the Tainan Sag, which are distributed across the areas of (from west to east) Tuyuke, Lukeqin, and Yingyeer: light oil (<0.9/cm3), heavy oil (0.9–0.93 g/cm3), extra-heavy oil (0.93–0.98 g/cm3), and ultra-heavy oil (>0.98 g/cm3). Notable differences were observed in the composition of these distinct crude oil types. As the densification degree of crude oil increases, the content of saturated hydrocarbon and aromatic hydrocarbon decreases gradually, and the content of asphaltene increases gradually. The light oil in the Tuyuke area of the Tainan Sag has undergone severe water washing and slight-to-moderate biodegradation. The extra-heavy oil in the Lukeqin area has undergone severe water washing but moderate-to-severe biodegradation. The ultra-heavy oil in the Yingyeer area has not undergone notable water washing but has been subjected to severe biodegradation. Biodegradation damages saturated hydrocarbons and aromatic hydrocarbons in crude oil to varying degrees, increasing the relative content of non-hydrocarbon constituents and asphaltenes and causing the oil to thicken gradually. This occurrence is highly common in areas of severe strata erosion. Water washing, usually occurring in the interlayers where oil and water are in contact with each other over a large area, causes densification of the oil by destroying the low-carbon aromatics in it. This study determined the geochemical characteristics, as well as the reservoir geology of crude oil under various causes of densification and, can serve as a scientific reference for research on the mechanisms of densification of crude oil in other locations.